Metastasis in oral cavity. Report in Chile of a metastatic breast cancer - Carlos Humeres Sigala; Anggie Véliz Amigo; Fatima Mota Arteaga; Sergio Vidal Gill (Brazilian Journal of Health Review, 2026)
Metastasis in the oral cavity is a rare event, constituting approximately 1% of all malignant pathologies located in this area. Breast cancer is a common type of cancer in women, but strangely it can produce metastases in the oral cavity. We present the case of a 77-year-old female patient, with a previous history of breast cancer and metastases in lung and brain, who came to the Regional Hospital of Antofagasta in 2020 to be evaluated in Oral Pathology for an ulcerated lesion with pain that did not heal. On clinical examination, an irregularly shaped lesion was observed in the right jugal mucosa. After histological and immunohistochemical analysis, was diagnosed as a metastasis of ductal breast carcinoma. Although it is an uncommon finding, it is the dentist's responsibility to investigate anomalies in the oral cavity that may refer to manifestations of other systemic pathologies, either diagnosed or that should be thoroughly evaluated in conjunction with other specialists to reach a diagnosis.